2018
DOI: 10.1038/s41419-018-1141-5
|View full text |Cite
|
Sign up to set email alerts
|

Plau and Tgfbr3 are YAP-regulated genes that promote keratinocyte proliferation

Abstract: Yes-associated protein (YAP) is a mechanosensor protein and a downstream effector of the Hippo kinase pathway, which controls organ growth, cell proliferation, survival, maintenance and regeneration. Unphosphorylated YAP translocates to the nucleus where it acts as a cofactor of primarily the TEAD transcription factors to activate target gene transcription and cell proliferation. Perturbed YAP activation results in tumorigenesis. The pathways downstream of activated YAP that drive cell proliferation remain rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 52 publications
(75 reference statements)
4
25
0
Order By: Relevance
“…RNA sequencing followed by gene set enrichment analysis of human keratinocyte cell lines transfected with YAP-5SA or YAP-specific siRNAs led to identification of YAP-regulated gene sets that included cell cycle reactomes (such as E2F targets or cyclin E-associated genes) and cell growth reactomes (including transcriptional cell cycle regulators such as Myc, and global translation regulators) [100], similar to what has been found in other cell types [73,74]. Interestingly, the epidermal transcriptome of K5 / YAP-5SA-ΔC transgenic mice was found to be enriched in genes that drive growth of cSCC cells [21,161]; consistent with the idea that aberrant YAP activation induces a premalignant tissue state that can progress further to neoplasia [99,136]. Among the key direct transcriptional targets of YAP/TAZ identified in the epidermis context are Cyr61 ( CCN1 ) [21,100,135], CTGF ( CCN2 ) [21,119], ITGB1 [100], TGFBR3 [161] and the Notch ligands DLL1 and JAG2 [119].…”
Section: Yap/taz Drive Proliferation Of Epidermal Scs and Fibroblamentioning
confidence: 97%
See 2 more Smart Citations
“…RNA sequencing followed by gene set enrichment analysis of human keratinocyte cell lines transfected with YAP-5SA or YAP-specific siRNAs led to identification of YAP-regulated gene sets that included cell cycle reactomes (such as E2F targets or cyclin E-associated genes) and cell growth reactomes (including transcriptional cell cycle regulators such as Myc, and global translation regulators) [100], similar to what has been found in other cell types [73,74]. Interestingly, the epidermal transcriptome of K5 / YAP-5SA-ΔC transgenic mice was found to be enriched in genes that drive growth of cSCC cells [21,161]; consistent with the idea that aberrant YAP activation induces a premalignant tissue state that can progress further to neoplasia [99,136]. Among the key direct transcriptional targets of YAP/TAZ identified in the epidermis context are Cyr61 ( CCN1 ) [21,100,135], CTGF ( CCN2 ) [21,119], ITGB1 [100], TGFBR3 [161] and the Notch ligands DLL1 and JAG2 [119].…”
Section: Yap/taz Drive Proliferation Of Epidermal Scs and Fibroblamentioning
confidence: 97%
“…However, it cannot be ruled out that YAP/TAZ might interact also with other TFs and coactivators involved in controlling epidermal SC functions, as there is evidence that YAP/TAZ form a nuclear complex with SMAD2/3 [160] and mediate nuclear accumulation of activated β-catenin [137] in a human keratinocyte cell line. Indeed, the hypoplastic abnormalities in the epidermis of K5 / YAP-5SA-ΔC transgenic mice were shown to involve activation of WNT16/β-catenin and TGF-β signalling [137,161,162] consistent with the well-established role of WNT and TGF-β signalling in controlling epidermal SC functions [163,164,165,166,167]. Although YAP is by default a transcriptional coactivator, it can also act as a corepressor in a complex with TEAD transcription factors and distinct chromatin-modifying proteins [76].…”
Section: Yap/taz Drive Proliferation Of Epidermal Scs and Fibroblamentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream target genes activated by YAP/TEAD that are involved in the proliferation of epidermal stem/progenitor cells include Plau and TGF-βr3 ( Corley et al, 2018 ), and Cyr61 ( Zhang et al, 2011 ), Hoxa1 and Hoxc13 ( Liu et al, 2015 ). Mendoza-Reinoso and Beverdam (2018) reported that WNT16 is upregulated in response to YAP activation in keratinocytes, resulting in promotion of keratinocyte proliferation via the canonical WNT16/β-catenin signaling pathway.…”
Section: Modulation Of Stem/progenitor Cell Lineage Fate By Yap/tazmentioning
confidence: 99%
“…Calcium is the major regulator of keratinocyte differentiation in vivo and in vitro [6], allowing the regulation of several genes [39,[61][62][63]. It was well known that the differentiation process is regulated by a number of biological signals derived from cell-cell or cell-matrix interactions that act downstream several signaling pathways [64,65] but, up to now, no detailed information about genes, proteins and metabolisms sequentially a b involved in the differentiation process, was reported in deep.…”
Section: Discussionmentioning
confidence: 99%